2015
DOI: 10.1161/atvbaha.115.305337
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group as a Model for Platelet Glycan Modification in Arterial Thrombosis

Abstract: ABO blood groups have long been associated with cardiovascular disease, thrombosis and acute coronary syndromes. Many studies over the years have shown type O blood group to be associated with lower risk of cardiovascular disease compared to non-type O blood groups. However, the mechanisms underlying this association remain unclear. Although ABO blood group is associated with variations in concentrations of circulating von Willebrand Factor and other endothelial cell adhesion molecules, ABO antigens are also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 77 publications
(77 reference statements)
2
30
0
Order By: Relevance
“…In addition, accumulating data have demonstrated that ABO blood group also influences risk for cardiovascular disease 37 . Although the mechanisms through which ABO impacts vascular risk remain poorly understood, recent evidence suggests that ABO(H) expression on platelets influences platelet function 5 , 6 , 25 . Our data highlight that there is significant inter-individual heterogeneity in platelet A antigen expression, even amongst healthy group A 1 donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, accumulating data have demonstrated that ABO blood group also influences risk for cardiovascular disease 37 . Although the mechanisms through which ABO impacts vascular risk remain poorly understood, recent evidence suggests that ABO(H) expression on platelets influences platelet function 5 , 6 , 25 . Our data highlight that there is significant inter-individual heterogeneity in platelet A antigen expression, even amongst healthy group A 1 donors.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the relationship between ABO and cardiovascular risk, it is important to emphasize that ABO(H) blood group determinants are expressed on a variety of different glycoproteins and glycolipids on the platelet surface 5 . It remains unclear whether the HXP/LXP effects apply equally to ABO(H) loading on each of these different platelet glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] Beyond the association with levels of circulating VWF, recent investigations have been focused on the capacity of ABO blood group antigens to influence serum levels of several inflammatory cytokines (i.e., tumor necrosis factor-α, soluble intercellular adhesion molecule 1, E-selectin, P-selectin, and interleukin 6), whose higher concentrations have been associated with an increased risk of cardiovascular thrombotic events. [40][41][42][43] Finally, the observations of the association between the ABO locus and plasma lipoprotein concentrations 44 and between non-O blood types and increased circulating cholesterol levels 45,46 add another important contribution to the understanding of the pathogenic mechanisms underlying the correlation between ABO blood group and coronary heart disease susceptibility. All in all, these data document that the relation between the ABO blood group system and cardiovascular diseases is more complex than the simple modulation of hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is for long known that ABO blood group antigens are present at the surface of platelets [2] and for nearly half a century, a link between ABO blood group antigens and cardiovascular disease was known [3]. ABO blood group is associated with many traits in addition to cardiovascular disease including platelet function parameters among healthy adults and patients with CAD [4,5].…”
mentioning
confidence: 99%